Funkcje przymiotnika przygodny w nazwach odmian gatunkowych tekstów religijnych - Żmigrodzka, Bożena (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2014)
The article is devoted to sub-genres of religious texts: sermons, prayers, and religious songs, which are called occasional sermon (kazanie przygodne), occasional prayer (modlitwa przygodna), and occasional religious song (pieśń przygodna), respectively. These sub-genres are intended for situations not included in the liturgical calendar, which occur in normal everyday life. By applying a proper religious text to these situations, they are supposed to gain a sacral dimension. The author analyzes the reasons for the decline in use of the adjective “przygodny” in favour of different terms, which complement the genre names “sermon” and “prayer”. She also tries to point out the reasons for the survival of the name “pieśń przygodna” up to the present day.